2006
DOI: 10.1080/15419060600631425
|View full text |Cite
|
Sign up to set email alerts
|

Local Ca2+Rise Near Store Operated Ca2+Channels Inhibits Cell Coupling During Capacitative Ca2+Influx

Abstract: Using a new fluorescence imaging technique, LAMP, we recently reported that Ca(2+) influx through store operated Ca(2+) channels (SOCs) strongly inhibits cell coupling in primary human fibroblasts (HF) expressing Cx43. To understand the mechanism of inhibition, we studied the involvement of cytosolic pH (pH(i)) and Ca(2+)([Ca(2+)](i)) in the process by using fluorescence imaging and ion clamping techniques. During the capacitative Ca(2+) influx, there was a modest decline of pH(i) measured by BCECF. Decreasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…In order to detect changes in molecular permeability of gap junction channels and to determine whether a cellular change can alter the gating property of connexin proteins, it is essential to assay dye transfer rates in the same coupled cell pairs before and after a biochemical stimulation in order to address if and how such an event affects cell coupling. Exploiting this important and unique property of LAMP assay, we demonstrated that Ca 2+ influx through store operated calcium channels potently inhibited GJ coupling 52 , likely mediated through a high subplasmalemmal Ca 2+ activity and colocalization of store operated Ca 2+ channel and connexin channel 58 .…”
Section: A New Class Of Caged Coumarins For Biological Imaging Appmentioning
confidence: 95%
See 2 more Smart Citations
“…In order to detect changes in molecular permeability of gap junction channels and to determine whether a cellular change can alter the gating property of connexin proteins, it is essential to assay dye transfer rates in the same coupled cell pairs before and after a biochemical stimulation in order to address if and how such an event affects cell coupling. Exploiting this important and unique property of LAMP assay, we demonstrated that Ca 2+ influx through store operated calcium channels potently inhibited GJ coupling 52 , likely mediated through a high subplasmalemmal Ca 2+ activity and colocalization of store operated Ca 2+ channel and connexin channel 58 .…”
Section: A New Class Of Caged Coumarins For Biological Imaging Appmentioning
confidence: 95%
“…Since HCCC2 emits blue fluorescence, it spectrally complements a variety of fluorescent sensors emitting from green to red. The combinatory use of these probes allow multi-color imaging to follow cellular biochemistry and cell coupling simultaneously 52, 58 .…”
Section: A New Class Of Caged Coumarins For Biological Imaging Appmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, LAMP has the combined advantages of both methods in that it is non-invasive, provides quantitative data, and has relatively high temporal resolution. In addition, LAMP allows for multicolor imaging, as the uncaging of NPE-HCCC2 requires a small pulse of UV light and is therefore compatible with fluorescent indicators in the visible spectrum ( Dakin et al, 2005 ; Dakin and Li, 2006 ; Abbaci et al, 2008 ). This method can be improved further by incorporating caged fluorescent molecules with higher uncaging efficiency and a more penetrable red-shifted emission spectrum.…”
Section: Transfer Of Tracersmentioning
confidence: 99%
“…This technique is mainly applied to study the dynamic regulation of gap junction coupling by intracellular Ca 2+ in individual cell pairs of human primary fibroblasts, for instance, and also to assess how Ca 2+ influx affects junctional coupling on HeLa cells expressing Cx26 (77,78). LAMP is limited to examination of changes in coupling in individual cell pairs, although it is likely to be useful in multiwell plate assays with confluent cell monolayers as well.…”
Section: Dye Transfermentioning
confidence: 99%